Metabarcoding gillnets to assess unaccounted catch depredation or escape. Issue 1 (30th June 2021) - de Bruyn, Mark; Barbato, Matteo; Broadhurst, Matt K.
Abstract: Gillnets are the world's most common net‐based fishing gear, comprising walls of light mesh designed to entangle fish. Gillnets are often retrieved with holes in the netting, which means some animals escape or are depredated unseen, but with some mortality. To effectively manage fisheries around the world, information is required on not only the harvested and discarded mortalities, but also problematic interactions and mortalities caused by the fishing gear and especially those involving protected species. This study sought to assess a novel method for determining such interactions by sampling five adjacent pieces of netting around each of ten holes in two bather‐protection polyethylene gillnets for environmental DNA or "eDNA". Here we show that eDNA correctly identified all previously entangled‐and‐landed species. Also, eDNA from three uncaptured taxa were recorded: bull shark, Carcharhinus leucas, white shark, Carcharodon carcharias and dolphins (Delphindae), illustrating the potential to reveal previously cryptic gillnet interactions. We propose that as scientific methods evolve and autonomous real‐time DNA surveillance becomes routine, eDNA testing of fishing gears and vessels could provide a novel, complementary fishery‐monitoring tool. Abstract : Here, we present the findings from a novel use of environmental (e)DNA: direct DNA metabarcoding of polyethylene gillnets targeting sharks (for bather protection). We show that some species, including white and bull sharks, and dolphins, cryptically interacted with the gillnets. Further, eDNA assays successfully identified all previously entangled‐and–landed taxa to at least the genus level.